ANALISIS TINGKAT KOGNITIF SOAL PADA MATERI STATISTIKA BUKU MATEMATIKA SMP KELAS VIII KURIKULUM 2013 - Sartika, Putri Dewi; Maizora, Syafdi; Siagian, Teddy Alfra; Susanto, Edi (JP2MS, 2021)
This study aimed to describe the cognitive level distribution of statistical questions based on the Revised Bloom Taxonomy. The type of this research is descriptive research. The data collection instrument was a classification sheet for the cognitive level of the questions. The data source in this study was a mathematics textbook, namely the mathematics book of Junior High School grade VIII of the 2013 curriculum, the 2017 revised edition compiled by Abdur Rahman Asy'ari, et al. Publisher Center for Curriculum and Books, Balitbang, Kemendikbud. Data collection by using the documentation method. The results showed that the distribution of cognitive levels in the statistical material questions was: C2-Understanding 11.36% (10 items), C3-Applying 82.96% (73 items), C4-Analyzing 4.54% (4 items). question), and C6-Creating 1.14% (1 item).